Contribution Of Pandit Deendayal Upadhyaya In Social Consciousness And Nation-Building (Journal of Namibian Studies : History Politics Culture, 2023)
Pandit Deen Dayal Upadhyaya's Integral Humanism is the moniker given to the Jan Sangh leader's philosophical concepts in the early 1960s. The ancient Indian heritage and cultural ethos have shaped the ideological outlines of holistic humanism. The underlying roots of Indian civilisation and Dharma created the philosophical moorings of integral humanism. By emphasising their innate disdain for humanitarian aspects of personal life and their overemphasis on the money factor, Upadhyaya has thoroughly dismantled capitalism and communism's social and political philosophies. As a result, integral humanism essentially believes in the ultimate authority of the Supreme, as well as a synergy of self, society, and the universe. According to Upadhyaya, every nation has its own cultural and socioeconomic core concept called as Chiti. Every community has its own set of characteristics classified as Virat. Every person has different responsibilities carved out for them and varying levels of activity. Integral humanism is defined as integrating these various facets of human life into a continuous interaction. We propose that this study identify the scattered ideological features of integral humanism and investigate the philosophy's contemporary significance in the context of seeking solutions to current political issues.